ANALISIS DAMPAK PENGGUNAAN GADGET TERHADAP KARAKTER RELIGIUS DAN SIKAP SOSIAL SISWA KELAS IV SD NEGERI 005 PALEMBANG - Rodhiyah, Nyayu Hujjatur; Hermansyah; Nuranisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
At SD Negeri 005 Palembang, the widespread use of gadgets among fourth-grade students is evident, mostly for entertainment, online games, and social media rather than learning. This study aims to describe the impact of gadget use on the religious character and social attitudes of fourth-grade students at SD Negeri 005 Palembang. A descriptive qualitative method was used, involving 54 students, 2 homeroom teachers, and 3 parents as informants, with data collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model and validated through triangulation. The results show that excessive gadget use reduces students' focus during religious activities, delays worship practices, and lowers direct social interaction, cooperation, and group participation. Conversely, when used wisely under parental and teacher supervision, gadgets can support learning and expand students' knowledge. It is concluded that gadget use has both positive and negative impacts, and consistent supervision from parents and teachers is essential to prevent the erosion of students' religious character and social attitudes.